Frequency and Outcome of isolated zygomatic arch fractures (IZAF) in Road traffic accident (RTA) patients - Saeed, Sahar; Khan, Ahmad; Ahmad, Junaid; Kumar, Muneesh; Khan, Zohaib Nasar; Inayat, Suneela (International Journal of Pathology, 2025)
Background: The zygomatic arch plays a key role in maintaining midfacial structure and aesthetics. Although isolated zygomatic arch fractures (IZAFs) represent only 5–10% of zygomaticomaxillary complex injuries, they can result in significant functional impairment and aesthetic deformity. This study aimed to evaluate the frequency and clinical outcomes of IZAFs in patients involved in road traffic accidents (RTAs) at a tertiary care hospital in Mardan Khyber Pakhtunkhwa Pakistan. Methods: A prospective observational study was conducted over six months from August 2024 to Feb 2025 at the Department of Oral and Maxillofacial Surgery, Mardan Medical Complex. A total of 145 patients with IZAFs confirmed by computed tomography CT scan were enrolled using non-probability consecutive sampling. The data were collected regarding the demographic characteristics and clinical presentation (including swelling, cosmetic deformity, trismus, and facial nerve weakness. Patients were followed at 1- and 3-months post-treatment. The outcome measures were evaluated based on mouth opening improvements (interincisal distance), facial contour symmetry restoration, and recovery of facial nerve function. Results: The mean age of the cohort was 30 ± 8 years. RTAs accounted for approximately 90% of the cases. All patients experienced pain at presentation, 60% had facial swelling, 40% exhibited trismus, 35% demonstrated cosmetic deformity, and 15% showed facial nerve weakness. Following treatment, the mean interincisal distance improved to 35 ± 4 mm at 1 month and 45 ± 3 mm at 3 months (p < 0.001), cosmetic deformity decreased to 10%, and facial nerve weakness reduced progressively from 15% at 4 weeks to 5% at 12 weeks (p < 0.05). Conclusion: Prompt and appropriate management using minimally invasive techniques leads to improvements in mouth opening, facial contour restoration, and recovery of facial nerve function.